Anticipating Challenges with In‐Building Disinfection for Control of Opportunistic Pathogens. (1st June 2014) - Rhoads, William J.; Pruden, Amy; Edwards, Marc A.
ABSTRACT: : A new American Society of Heating, Refrigerating and Air‐Conditioning Engineers (ASHRAE) standard for control of Legionella (ASHRAE Standard 188, 2013) emphasizes use of in‐building disinfection techniques to reduce the exposure of at‐risk consumers to opportunistic pathogens in premise plumbing (OPPPs). This standard and other recommendations for OPPP control have implications for scaling in and corrosion of plumbing systems, which can sometimes adversely affect the efficacy of the disinfection method and physical integrity of the plumbing system, prompting this proactive critical review of challenges associated with implementation of Standard 188.